Ras-related C3 botulinum toxin substrate 1 activation is involved in the pathogenesis of diabetic retinopathy - LI, YANG-JUN (Exp Ther Med, 2015)
This study used a streptozotocin (STZ)-induced rat model of diabetes to investigate whether Ras-related C3 botulinum toxin substrate 1 (Rac1) was involved in the pathogenesis of diabetic retinopathy. The effects of Rac1 inhibition on vascular endothelial (VE)-cadherin and β-catenin expression in high glucose-induced rat retinal endothelial cells (RRECs) were additionally examined. Rac1 activation in the retinas from STZ-induced diabetic rats and in high glucose-induced RRECs was measured by reverse transcription-quantitative polymerase chain reaction analysis, immunohistochemistry and western blot analysis. The expression levels of VE-cadherin and β-catenin were also examined with or without Rac1 inhibition through small interfering (si)RNA transfection. STZ-induced diabetes was associated with an increase in the vascular permeability of the retina. Furthermore, Rac1 activation was increased in the retina of STZ-induced diabetic rats and in high glucose-induced RRECs compared with that in the controls. Immunohistochemistry showed that immunostaining of Rac1 was localized in the outer plexiform, inner nuclear, inner plexiform and ganglion cell layers and in the retinal microvasculature of rats. The expression of β-catenin was increased in the retinas of the diabetic rats at four, eight and 12 weeks after the induction of diabetes compared with that in the controls. Additionally, Rac1 activation was required for the high glucose-induced VE-cadherin expression decrease and for β-catenin expression in high glucose-induced RRECs. Rac1 inhibition by Rac1-siRNA transfection effectively prevented hyperpermeability, β-catenin expression and the VE-cadherin expression decrease in high glucose-induced RRECs. In conclusion, diabetes affects the expression of Rac1 in the retina. Rac1 may be involved in the diabetes-induced damage and/or alterations to the blood-retinal barrier through changes in VE-cadherin and β-catenin expression.